Daylighting Evaluation of Perforated Screen Façade with Light Shelf in the Tropics - Feny Elsiana; Lilianny S Arifin (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2024)
The use of large glass facades in buildings without external shading devices leads to a high daylight level, uneven daylight distribution, and glare. A perforated screen facade (PSF) is one of the shading systems that can provide daylight and view and prevent direct solar radiation into a building. More research is needed about the daylight performance of PSF in integration with daylighting systems in the tropics. A combination of PSF and light shelf (LS), a daylighting system that can redirect daylight to the ceiling and enhance daylight distribution, is proposed to improve daylight levels and reduce glare. The research aims to evaluate the daylight performance of PSF and LS in the tropics. The research method is experimental with simulation utilizing IES-VE Radiance IES. Average Daylight Factor (DFavg), Useful Daylight Illuminance (UDI), and Daylight Glare Probability (DGP) of a room with a side window were compared with a room with PSF and LS. The results showed that implementing PSF and LS improved daylight performance by lowering the DFavg by 55%, increasing the UDI, and reducing the DGP.